Long‐lived Snell dwarf mice display increased proteostatic mechanisms that are not dependent on decreased mTORC1 activity. Issue 3 (26th February 2015) - Drake, Joshua C.; Bruns, Danielle R.; Peelor, Frederick F.; Biela, Laurie M.; Miller, Richard A.; Miller, Benjamin F.; Hamilton, Karyn L.
Summary Maintaining proteostasis is thought to be a key factor in slowed aging. In several growth‐restricted models of long‐life, we have shown evidence of increased proteostatic mechanisms, suggesting that proteostasis may be a shared characteristic of slowed aging. The Snell dwarf mouse is generated through the mutation of the Pit‐1 locus causing reductions in multiple hormonal growth factors and mTORC1 signaling. Snell dwarfs are one of the longest lived rodent models of slowed aging. We hypothesized that proteostatic mechanisms would be increased in Snell compared to control (Con) as in other models of slowed aging. Using D2O, we simultaneously assessed protein synthesis in multiple subcellular fractions along with DNA synthesis in skeletal muscle, heart, and liver over 2 weeks in both sexes. We also assessed mTORC1‐substrate phosphorylation. Skeletal muscle protein synthesis was decreased in all protein fractions of Snell compared to Con, varied by fraction in heart, and was not different between groups in liver. DNA synthesis was lower in Snell skeletal muscle and heart but not in liver when compared to Con. The new protein to new DNA synthesis ratio was increased threefold in Snell skeletal muscle and heart compared to Con. Snell mTORC1‐substrate phosphorylation was decreased only in heart and liver. No effect of sex was seen in this study. Together with our previous investigations in long‐lived models, we provide evidence further supporting proteostasis as a shared characteristic of slowed aging and show that increased proteostatic mechanisms may not necessarily require a decrease in mTORC1.